2019
DOI: 10.4209/aaqr.2018.09.0350
|View full text |Cite
|
Sign up to set email alerts
|

Sources of High Sulfate Aerosol Concentration Observed at Cape Hedo in Spring 2012

Abstract: Intensive observation campaigns approximately 1 week long were conducted periodically from March 2010 to November 2015 at Cape Hedo, Okinawa, Japan. The maximum daily mean sulfate aerosol (SO 4 2-) concentrations surpassed 15 µg m -3 in spring 2012. In this study, source apportionment for these high concentrations was conducted using an air quality model with the tagged tracer method, and the main source was identified as volcanoes in March and as anthropogenic emissions from China in April. In March, the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…2concentrations simulated in domain 1 of J-STREAM are shown in Figure 1, based on averaging of the entire monitoring period. The high concentrations of SO 4 2over the Asian continent that included the downwind region of Japan were related to transboundary SO 4 2in Japan as discussed previously [30][31][32][33][34]. The differences in distributions of SO 4 2between the base-case simulations and those for the chemistry updates A and KMT are clearly evident.…”
Section: Model Performancesupporting
confidence: 54%
“…2concentrations simulated in domain 1 of J-STREAM are shown in Figure 1, based on averaging of the entire monitoring period. The high concentrations of SO 4 2over the Asian continent that included the downwind region of Japan were related to transboundary SO 4 2in Japan as discussed previously [30][31][32][33][34]. The differences in distributions of SO 4 2between the base-case simulations and those for the chemistry updates A and KMT are clearly evident.…”
Section: Model Performancesupporting
confidence: 54%
“…All available observation data were used in this study. As we have discussed in previous work (Itahashi et al, 2020a), Asian air pollution can impact on air quality over the USA; however, the magnitude of volcanic emissions on tropospheric SO 2− 4 levels over North America has not been well studied. To evaluate the impact of volcanic SO 2 emissions located in the Northern Hemisphere on model performance, surface observations over the USA were obtained from the Clean Air Status and Trends Network (CASTNET), which covered remote and rural sites mostly over eastern USA (CASTNET, 2020), and the Integrated Monitoring of Protected Visual Environments (IMPROVE), which covered remote sites mostly over western USA (IMPROVE, 2020).…”
Section: Ground-based Observationsmentioning
confidence: 96%
“…Finally, the impacts caused by including the degassing volcanoes were investigated throughout the troposphere. In a subsequent analysis, the boundary layer is defined from the surface to 750 hPa, and the free troposphere is defined from 750 to 250 hPa, and pressure levels of 750, 500, and 250 hPa are used to refer to the bottom, middle, and top of the free troposphere similar to our previous study (Itahashi et al, 2020a). The vertical profile of simulated SO 2− 4 concentration averaged along the edge of western USA (defined in Fig.…”
Section: Impact On Upper Tropospherementioning
confidence: 99%
“…Numerical modeling is a useful tool to characterize source-receptor relationships. Regional modeling studies have already indicated that volcanic SO2 emissions are one of the main sources of SO4 2over Japan (Itahashi et al, 2017a;2017b;Itahashi, 2018;Itahashi et al, 2019). SO2 emissions from volcanos in the Pacific Rim region not only regulate tropospheric SO4 2levels in surrounding countries but through long-range transport can also potentially impact SO4 2distributions over the Pacific and background levels in the western U.S.A. Liu et al (2008) for instance suggest that west to east across the North Pacific, sulfate originating from East Asia sources contributed approximately 80%-20% of sulfate at the surface, but at least 50% at 500 hPa.…”
Section: Introductionmentioning
confidence: 99%